Is the Leptin/Adiponectin Ratio a Better Diagnostic Biomarker for Insulin Resistance than Leptin or Adiponectin Alone in Adolescents? - César Agostinis-Sobrinho; Sofia E. de Castro Ferreira Vicente; Sigute Norkiene; Alona Rauckienė-Michaelsson; Justina Kievisienė; Viney Prakash Dubey; Arturas Razbadauskas; Luís Lopes; Rute Santos (MDPI AG, 2022)
Background: Recently, the leptin/adiponectin (L/A) ratio has been suggested as a novel predictor of cardio-metabolic and other chronic diseases. Aim: To evaluate the ability of leptin (L), adiponectin (A), and the L/A ratio in identifying high risk of insulin resistance IR in adolescents, adjusted by cardiorespiratory fitness, adherence to the Mediterranean diet, and body fat percentage. Subjects and methods: This is a cross-sectional analysis with 529 adolescents aged 12-18 years-old. Blood samples were taken to analyze glucose, insulin, leptin, and adiponectin levels. IR (homeostasis model assessment of insulin resistance (HOMA-IR) was estimated from fasting serum insulin and glucose). Results: Adiponectin, leptin, and L/A ratio were accurate to predict IR among adolescents. The optimal L/A cut-off value to indicate risk of IR development was >0.35 in boys and >0.97 in girls. Logistic analyses showed that the suggested cut-off points for adiponectin (girls: OR: 2.87 (1.26-6.53); p = 0.012); leptin (boys: OR: 5.23 (1.16-7.14) p = 0.006; girls: OR: 2.99 (1.10-8.09) p = 0.031), and the L/A ratio (boys: OR: 8.38 (2.6-26.8) p < 0.001; girls: OR: 6.1 (2.1-17.0) p < 0.001), were significant predictors of IR, after adjustments for age, pubertal stage, adherence to the Mediterranean diet, cardiorespiratory fitness, and body fat percentage. Conclusion: Leptin and L/A ratio were associated with IR risk, after adjustments for confounders in both sexes and adiponectin in girls. The L/A ratio seems to have a higher diagnostic accuracy to identify IR risk than adiponectin or leptin, in both sexes.